Ion and Electron Kappa Distribution Functions Along the Plasma Sheet - Espinoza-Romo, C; Stepanova, M (American Geophysical Union, 2018)
We use kappa distributions to model thousands of ion and electron flux spectra along the plasma sheet and analyze the variation of the spectral index and the temperature T in this region. We find that distributions are ubiquitous and fit well ion and electron flux spectra during quiet times, and during the expansion and recovery phases of substorms. Near Earth, and up to similar to 12 R-E, the indices are different than the rest of the plasma sheet, both for ions (kappa(i)) and electrons (kappa(e)). There is a significant dawn-dusk asymmetry in kappa(i) toward the tail, which is enhanced during substorms. The ions also exhibit a permanent temperature asymmetry, determined by a colder dawnside. The whole tail becomes hotter during substorms, but it appears that most of the energy is deposited near Earth. Plain Language Summary Ions and electrons in space plasmas rarely experience collisions and the only way they exchange energy is via electromagnetic interactions. It is said that these plasmas are out of thermal equilibrium, which is the ground state of most systems, and can be compared to the balance of temperatures observed when two bodies are in contact. In the Earth s magnetosphere, plasmas are constantly energized by geomagnetic storms and substorms. Because of all this, and contrary to most materials on Earth, particles outside the Earth are always out of thermal equilibrium and their energy budgets are difficult to describe. We have studied ions and electrons in the magnetotail of the Earth s magnetosphere using data taken by the Time History of Events and Macroscale Interactions during Substorms satellites. We confirmed that particles are out thermal equilibrium and found that their behavior is not entirely random, but somewhat organized, even during substorms. They follow the so called kappa functions. This means that particles somehow have an efficient way to organize themselves. We think our findings can provide scientist with better ways to characterize particles in this area of the magnetosphere and build more reliable models.